1991
DOI: 10.1051/forest:19910404
|View full text |Cite
|
Sign up to set email alerts
|

Modélisation de la croissance des peuplements réguliers de hêtre : dynamique des hiérarchies sociales et facteurs de production

Abstract: Résumé — Afin de permettre la simulation de la croissance de peuplements réguliers de hêtre soumis à divers traitements sylvicoles, un modèle indépendant des distances a été mis au point, à partir des données recueillies dans des essais comparatifs d'éclaircie observés sur de longues périodes. On a choisi de modéliser simultanément et de façon cohérente l'effet de la densité et des facteurs sociaux sur la croissance, aux deux niveaux de l'arbre et du peuplement. Le

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Indeed if data is related to periods between 3 and 7 years, facility in using simulation software can quickly lead to annual reiterations of the model, or on the contrary to very large increment simulations (more than 10 years). As already studied by Dhôte [8], period length does not have a strong effect, except outside the data framework, i.e. for increments less than 3 years or more than 7 years.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed if data is related to periods between 3 and 7 years, facility in using simulation software can quickly lead to annual reiterations of the model, or on the contrary to very large increment simulations (more than 10 years). As already studied by Dhôte [8], period length does not have a strong effect, except outside the data framework, i.e. for increments less than 3 years or more than 7 years.…”
Section: Discussionmentioning
confidence: 83%
“…Dhôte [7,8] proposed a segmented linear model between individual basal area increment and initial circumference at breast height (initially for beech, then for oak). It has an initial part of null growth for understorey trees and an increasing growth part for main vegetation storey trees.…”
Section: State Of the Artmentioning
confidence: 99%
“…This interval indicates a rather conservative silviculture; previous work has shown that, for a given age, stand basal area or dominant height growth rates are almost independent on density, in this range of densities (Dhôte, 1991 The estimation procedure is a modification of that used by Dhôte and de Hercé (1994 (Dhôte, 1992 Although there is no single total volume yield-height relationship for all the forests (see Assmann, 1955) and although total yield may vary at a given height when site index varies (coherent with Kennel, 1973) This expression is a conventional balance between a positive term, which is proportional to dominant height, and a negative term proportional to the square power of height. This looks very much like the carbon-balance models, where the positive term represents the allocation of photosynthates to stem and branch growth and the negative term the losses of carbon due to mortality and maintenance respiration (Linder et al, 1985;Valentine, 1985;Mäkelä, 1986 Kira, 1975, cited by Cannell, 1989;Yokoi et al, 1978;Frossard and Lacointe, 1991).…”
Section: Objectives Of This Studymentioning
confidence: 99%
“…This study on productivity is part of a larger project aimed at modeling growth of pure even-aged stands of common beech, on the basis of a network of permanent plots observed since the turn of the century (Dhôte, 1991 Germany (Schober, 1972) and at the data discussed by Kennel (1973) revealed that none of these 2 sources verified Eichhorn's rule (Dhôte, 1992 Arbonnier (1958), Pardé (1962Pardé ( , 1981 and Oswald and Divoux (1981).…”
Section: Objectives Of This Studymentioning
confidence: 99%
“…The model was designed in the 1990s [25,26] and was largely described by Le Moguédec and Dhôte [27]. In brief, the model uses a top-down approach to predict forest growth over three-year growth intervals.…”
Section: Growth Modelmentioning
confidence: 99%